Architects of electronic trading : technology leaders who are shaping today's financial markets - Hammer-Krabbe, Stephanie, 1974- (Hoboken : Wiley, 2013)
Insights that can help you improve your technology edge Featuring contributions from technology visionaries at leading alternative investors, hedge funds, trading firms, exchanges, and vendors, this book covers current trends in trading technology. The book features interviews with the leaders responsible for the technology that is shaping today's electronic financial markets. You'll hear the views of CIOs, CTOs, and other technology leaders on emerging technologies, innovation in the financial sector, and how technology is enhancing markets in ways other than just speed. Their perspe.
Foreword -- Acknowledgments -- About the author -- Meet the architects -- Business challenges -- Laying a strong foundation with transformational technology -- Hardware acceleration with FPGAS -- Conclusion: a call for continued education -- Index.
Includes index.
Print version record and CIP data provided by publisher.
Keywords: Electronic trading of securities; Investments -- Computer network resources; Electronic trading of securities; Investments -- Computer network resources; BUSINESS & ECONOMICS -- E-Commerce -- Online Trading; Electronic trading of securities; Investments -- Computer network resources; Electronic trading of securities; Investments / Computer network resources; Electronic books